Outcome-Based Arabic Language Education: Leveraging Learning Analytics for Graduate Success - Samin, Saproni Muhammad; Zakaria, Gamal Abdul Nasir; Pebrian, Rojja (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study evaluates an Arabic Language Education Program's Outcome‑Based Education (OBE) implementation using a Goal‑Free Evaluation Model (GFEM). The research objectives were to: (1) link Graduate Learning Outcomes (GLO) with Course Learning Outcomes (CLO) and assessments, (2) appraise Student‑Centered Learning (SCL), authentic assessment, and facilities/IT support, and (3) synthesize educational outputs and graduate employability. The methodology employed a convergent, multi‑source design triangulating curriculum records, satisfaction and employer surveys, tracer coverage, academic indicators, research/engagement portfolios, facilities/IT audits, and stakeholder interviews conducted from 2022 to 2024. The results demonstrate consistent implementation from planning to outcomes: GLOs cascade effectively to CLOs; SCL (problem, project, case‑based) is routinely implemented; micro‑teaching is institutionalized across the program. Key findings include GPA 3.73, time‑to‑degree 3.8 years, on‑time graduation 52%, tracer coverage 92.86%, employability/entrepreneurship/further study 97.5%, and 4.8‑month waiting time. The study concludes that identity‑rooted OBE improvements with global responsiveness are achievable through systematic implementation, continuous monitoring, and cultural integration within educational frameworks.